2018
DOI: 10.1088/1361-6552/aac487
|View full text |Cite
|
Sign up to set email alerts
|

A primer to numerical simulations: the perihelion motion of Mercury

Abstract: Numerical simulations are playing an increasingly important role in modern science. In this work it is suggested to use a numerical study of the famous perihelion motion of the planet Mercury (one of the prime observables supporting Einsteins General Relativity) as a test case to teach numerical simulations to high school students. The paper includes details about the development of the code as well as a discussion of the visualization of the results. In addition a method is discussed that allows one to estima… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Although the work of Koerber et al is ambitious, we do not think that it achieves its goal of being accessible to high school students (or even most undergraduates) and that the treatment in terms of the coding is unnecessarily complicated. Obviously, there is the important exception of many European countries where the use of Python and writing of computer programs is an obligatory part of the physics curriculum [10]. In their work, it was stated that they wished to communicate the beauty of theoretical physics to beginner students with an important historical example, but the amount of detail provided was perhaps overwhelming for students approaching this topic for the first time.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the work of Koerber et al is ambitious, we do not think that it achieves its goal of being accessible to high school students (or even most undergraduates) and that the treatment in terms of the coding is unnecessarily complicated. Obviously, there is the important exception of many European countries where the use of Python and writing of computer programs is an obligatory part of the physics curriculum [10]. In their work, it was stated that they wished to communicate the beauty of theoretical physics to beginner students with an important historical example, but the amount of detail provided was perhaps overwhelming for students approaching this topic for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…In common with [10], we have shown that Maple can be used to visualise the precession of the orbit of a light body due to relativistic corrections. However, we can now go further and make a quantitative connection with the precession of Mercury (in [10] this part of the analysis was considered to be for advanced students only). To begin, we need to find the angular positions f 1 , f 2 , f 3 and f 4 of the first four perihelia in figure 1 (right).…”
Section: Quantifying the Precession For Mercurymentioning
confidence: 94%
See 3 more Smart Citations